2020
DOI: 10.3390/nu12030863
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Complications of Oropharyngeal Dysphagia in Older Patients with Dementia

Abstract: The prevalence of older patients with dementia and oropharyngeal dysphagia (OD) is rising and management is poor. Our aim was to assess the prevalence, risk factors, and long-term nutritional and respiratory complications during follow-up of OD in older demented patients. We designed a prospective longitudinal quasi-experimental study with 255 patients with dementia. OD was assessed with the Volume-Viscosity Swallowing Test and a geriatric evaluation was performed. OD patients received compensatory treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 46 publications
1
61
1
6
Order By: Relevance
“…Accordingly, OD has been considered an indicator of frailty [ 3 ] and dependence [ 4 ] and is currently recognized as a geriatric syndrome [ 5 , 6 ]. Currently, the prevalence of OD in the world population is 16–23% and increases to 30% in older people [ 7 , 8 , 9 ]; it increases even further in the presence of dementia [ 4 , 6 ], reaching a prevalence of up to 85.9% in Spain [ 10 ]. In Europe, the prevalence of OD in the over-65s is 40%, and in institutionalized elderly people, it is more than 60% [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, OD has been considered an indicator of frailty [ 3 ] and dependence [ 4 ] and is currently recognized as a geriatric syndrome [ 5 , 6 ]. Currently, the prevalence of OD in the world population is 16–23% and increases to 30% in older people [ 7 , 8 , 9 ]; it increases even further in the presence of dementia [ 4 , 6 ], reaching a prevalence of up to 85.9% in Spain [ 10 ]. In Europe, the prevalence of OD in the over-65s is 40%, and in institutionalized elderly people, it is more than 60% [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…They developed reduced pharyngeal clearance, reduced upper esophageal opening, and penetration and/or aspiration as the disease progresses [49]. Some epidemiological studies reported that dementia was one of the main risk factors for dysphagia and aspiration pneumonia [17,50]. Moreover, the prevalence of dysphagia was high among schizophrenic patients due to the nature of schizophrenia and the side effects of antipsychotic medication [44, 51, and52].…”
Section: Discussionmentioning
confidence: 99%
“…Several original international studies [5][6][7][8][9][10][11][12][13][14] and one meta-analysis [15] reported that the oral health status of psychiatric patients was poor compared to that of the general population. In addition, some previous studies reported that patients with schizophrenia and dementia had poor swallowing function and were at risk for aspiration pneumonia [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…They developed reduced pharyngeal clearance, reduced upper esophageal opening, and penetration and/or aspiration as the disease progresses [44]. Some epidemiological studies reported that dementia was one of the main risk factors for dysphagia and aspiration pneumonia [45,46]. Moreover, the prevalence of dysphagia was high among schizophrenic patients due to the nature of schizophrenia and the side effects of antipsychotic medication [39, 47, and 48].…”
Section: Discussionmentioning
confidence: 99%